Percutaneous K-wires vs palmar locking plate fixation for different types of distal radial fractures: a comparison of the outcomes of two methods to controll our guidelines - Zyluk, Andrzej; Janowski, Piotr; Szlosser, Zbigniew; Puchalski, Piotr (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2018)
The objective of the study was a comparison of the outcomes of K-wire vs plate fixation for distal radial fractures used according to the proposed institutional algorithm. Fracture configurations A2, A3, B1, B2, C1 and some C2 were operated on with K-wire pinning, whereas B3 and some B2, C3 and some C2 were with locking palmar-plate fixation.Patients and Methods: Four hundred and sixty-seven patients were non-randomly allocated for either K-wire (n = 363) or palmarplate (n = 104) fixation. The results were assessed at 3 and 12 months by the same outcome measures.Results: At the 3-month assessment, statistically significant differences in grip strength and the DASH scores were noted in favour of the plate-fixation group. At the 12-month assessment, statistically significant differences were observed in the wrist palmar and dorsal flexion, favouring the plate-fixation group. Statistically significant differences were noted in radiological measures of the palmar tilt and the ulnar variance, both favouring the plate-fixation method. Meaningful secondary dislocations were noted in ten patients, all in the K-wire-fixation group.Conclusion: We conclude that palmar locking plate fixation in even more severe fractures leads to better radiological and clinical outcomes than K-wire fixation in less severe fractures.
Keywords: Distal radius fracture; K-wire fixation; locking plate fixation